(untitled) (Annals of Medical Research, 2023)
Aim: COVID-19 pandemic which has disrupted the daily routine and professional life of every individual including professional athletes from every branch. In addition to the postponed race programme COVID-19 itself may cause anxiety and sleep problems which have the potential to further impair sport performance. This study aimed to determine level of anxiety and sleep status of sportsmen during the pandemic. Materials and Methods: On line questionnaires addressing sleep and anxiety was posted to the athletes who were engaged in eight different sport branches (football, basketball, volleyball, athletics, boxing, kickboxing, tennis and badminton) responded to provide data to this study. Responses obtained through an online questionnaire conducted between April and May 2020 were evaluated. Pittsburgh Sleep Quality Index (PSQI) inventory was utilized to measure the quality of sleep and State and Trait-Anxiety Inventories (STAI-S, STAI-T) and Generalized Anxiety Disorder-7 (GAD-7) inventories were used for examining the anxiety level, quantitatively. Results: A total of 343 athletes (129 women and 214 men, mean age: 23.16 ± 0.43 yr; mean body mass index: 22.88 ± 0.12 kg/m2) responded to the survey. The overall mean PSQI score was 5.96 ± 0.12, and athletics were the most affected group by the sleep quality (6.85 ± 0.35, p = 0.038). Mean PSQI scores revealed low sleep quality during pandemic (5.96 ± 0.12), and athletics were the most affected group by the sleep quality (6.85 ± 0.35, p = 0.038). Regarding state anxiety (STAI-S), athletes had border-line anxiety levels (41.11 ± 0.21), their trait anxiety (STAI-T) score was 38.91 ± 0.22 (n=343) for overall participants. According to the GAD-7 scores the athletics had mild anxiety level (8.15 ± 0.21), kickboxers being most affected group with GAD-7 scores of 9.26 ± 0.62, (p < 0.001 vs other athletes, n=35). Conclusion: This cross-sectional study indicate that there was a poor sleep quality and a mild level of anxiety among sportsman during the pandemic.